Synthetic strigolactone analogues reveal anti-cancer activities on hepatocellular carcinoma cells. Issue 6 (1st April 2018) - Hasan, Mohammed Nihal; Choudhry, Hani; Razvi, Syed Shoeb; Moselhy, Said Salama; Kumosani, Taha Abduallah; Zamzami, Mazin A.; Omran, Ziad; Halwani, Majed A.; Al-Babili, Salim; Abualnaja, Khalid Omer; Al-Malki, Abdulrahman Labeed; Alhosin, Mahmoud; et al.
Graphical abstract: Abstract: Hepatocellular carcinoma (HCC) remains one of the leading causes of death worldwide. The complex etiology is attributed to many factors like heredity, cirrhosis, hepatitis infections or the dysregulation of the different molecular pathways. Nevertheless, the current treatment regimens have either severe side effects or tumors gradually acquire resistance upon prolonged use. Thus, developing a new selective treatment for HCC is the need of the hour. Many anticancer agents derived from plants have been evaluated for their cytotoxicity towards many human cancer cell lines. Strigolactones (SLs)-a newly discovered class of phytohormones, play a crucial role in the development of plant-root and shoot. Recently, many synthetic analogues of SLs have demonstrated pro-apoptotic effects on different cancer cell lines like prostate, breast, colon and lung. In this study, we tested synthetic SLs analogues on HCC cell line-HepG2 and evaluated their capability to induce cell proliferation inhibition and apoptosis. Primary WST-1 assays, followed by annexin-V/7AAD staining, demonstrated the anti-proliferative effects. The SLs analogues TIT3 and TIT7 were found to significantly reduce HepG2 cell viability in a dose- and time-dependent manner and induce apoptosis. Interestingly, though TIT3 and TIT7 strongly affected cancer cell proliferation, both compounds showed moderate anti-proliferative effect on normal cells. Further, migration of cancer cells was suppressed upon treatment with TIT3 and TIT7 in a wound healing assay. In summary, these findings suggest that two SLs analogues TIT3 and TIT7 exert selective inhibitory effects on cancer cells most likely through targeting microtubules. SLs analogues could be used in future as potential anti-cancer candidates in chemotherapy.